Phosphodiesterase-4 enzyme as a therapeutic target in neurological disorders. (October 2020) - Bhat, Abid; Ray, Bipul; Mahalakshmi, Arehally Marappa; Tuladhar, Sunanda; Nandakumar, DN; Srinivasan, Malathi; Essa, Musthafa Mohamed; Chidambaram, Saravana Babu; Guillemin, Gilles J.; Sakharkar, Meena Kishore
Graphical abstract: Abstract: Phosphodiesterases (PDE) are a diverse family of enzymes (11 isoforms so far identified) responsible for the degradation of cyclic adenosine monophosphate (cAMP) and cyclic guanosine monophosphate (cGMP) which are involved in several cellular and biochemical functions. Phosphodiesterase 4 (PDE4) is the major isoform within this group and is highly expressed in the mammalian brain. An inverse association between PDE4 and cAMP levels is the key mechanism in various pathophysiological conditions like airway inflammatory diseases−chronic obstruction pulmonary disease (COPD), asthma, psoriasis, rheumatoid arthritis, and neurological disorders etc. In 2011, roflumilast, a PDE4 inhibitor (PDE4I) was approved for the treatment of COPD. Subsequently, other PDE4 inhibitors (PDE4Is) like apremilast and crisaborole were approved by the Food and Drug Administration (FDA) for psoriasis, atopic dermatitis etc. Due to the adverse effects like unbearable nausea and vomiting, dose intolerance and diarrhoea, PDE4 inhibitors have very less clinical compliance. Efforts are being made to develop allosteric modulation with high specificity to PDE4 isoforms having better efficacy and lesser adverse effects. Interestingly, repositioning PDE4Is towards neurological disorders including Alzheimer's disease (AD), Parkinson's disease (PD), Huntington's disease (HD), multiple sclerosis (MS) and sleep disorders, is gaining attention. This review is an attempt to summarize the data on the effects of PDE4 overexpression in neurological disorders and the use of PDE4Is and newer allosteric modulators as therapeutic options. We have also compiled a list of on-going clinical trials on PDE4 inhibitors in neurological disorders.